Fatty acids composition in oils from several species of tetraodontidae (puffer fish) - Nursyafiqah, Elias (Universiti Malaysia Sarawak (UNIMAS), 2015)
Polyunsaturated fatty acids (PUFAs) are well known with its various benefits to human health especially in reducing cardiovascular diseases, reducing the potential of diabetes and many more. This study was carried out to determine the fatty acids composition from several species of puffer fish such as Lagocephalus lunaris, L. spadiceus, L. sceleratus, Xenopterus naritus, Ostracion nasus and Chelonodon patoca. C. patoca has the highest value of ash and moisture content with 80.41% and 4.25%, respectively while L. lunaris has the highest total organic matter with 97.47 % from the proximate analysis. In general, liver contain the highest oil composition compared to muscle tissue as more fatty acids compound detected in the liver. This study also revealed that monounsaturated fatty acids with cis-10-heptadecenoic acid (C17:1) is the most compound formed. The chemometric analysis on fatty acids data revealed that L. spadecius, X. naritus and O. nasus species showed large similarity while L. sceleratus was very distinct to the other species in terms of fatty acid composition.